HIV epidemiology and challenges in prevention, testing and treatment in Eastern Europe and Central Asia from a mixed-method review - Machiko Otani; Soudeh Ehsani; Viatcheslav Grankov; Stela Bivol; Giorgi Kuchukhidze (Discover Public Health, 2026)
Abstract Objective Eastern Europe and Central Asia (EECA) is experiencing a rise in the number of new HIV infections and is lagging in reaching the testing and treatment cascade targets. We aimed to identify gaps in prevention, testing, and treatment services, with a focus on key populations (KPs), and propose key actions for the EECA region to achieve the goal of ending AIDS by 2030. Methods A mixed-method review was conducted. Quantitative data, covering 15 EECA countries, were extracted from the standardised global and regional data collection systems, as well as a regional survey on HIV surveillance. Qualitative insights were drawn from WHO HIV Programme Reviews conducted in 2022 to 2024 across nine countries: Albania, Azerbaijan, Belarus, Georgia, Kyrgyzstan, the Republic of Moldova, Tajikistan, Ukraine, and Uzbekistan. Epidemic patterns, surveillance systems, policies, service delivery, KP size estimation, prevention coverage, and HIV status awareness among KPs were analysed. Findings While progress has been observed, none of the countries has achieved the UNAIDS 95‑95‑95 targets. Common challenges identified across EECA included persistent late diagnosis, patterns suggestive of possible misclassification of transmission modes, underutilisation of routinely collected data, limited implementation of innovative policies and approaches, suboptimal prevention coverage and awareness of HIV status among KPs, and high levels of stigma. By integrating quantitative indicators with evidence from the WHO HIV Programme Reviews, this study provides additional insight into how implementation‑level constraints shape observed epidemiological patterns across EECA. Conclusion In EECA, while much progress has been made in the last decade, many gaps and challenges in HIV prevention, testing, and treatment impede effective control of HIV. Identified priority actions should be promoted to contain the fast-growing HIV infection and achieve ending AIDS by 2030.